Phenotypic and Functional Dysregulated Blood NK Cells in Colorectal Cancer Patients Can Be Activated by Cetuximab Plus IL-2 or IL-15 - Rocca, Yamila Sol; Roberti, María Paula; Juliá, Estefanía Paula; Pampena, María Betina; Bruno, Luisina; Rivero, Sergio; Huertas, Eduardo; Sánchez Loria, Fernando; Pairola, Alejandro; Caignard, Anne; Mordoh, José; Levy, Estrella Mariel (Frontiers in Immunology, 2016)
The clinical outcome of colorectal cancer (CRC) is associated with the immune response, thus these tumors could be responsive to different immune therapy approaches. NK cells are key anti-tumor primary effectors that can eliminate CRC cells without prior immunization. We previously determined that NK cells from the local tumor environment of CRC tumors display a profoundly altered phenotype compared to circulating NK cells from healthy donors. In this study, we evaluated peripheral blood NK cells from untreated patients and their possible role in metastasis progression. We observed profound deregulation in receptor expression even in early stages of disease compared to healthy donors. CRC-NK cells displayed under-expression of CD16, NKG2D, DNAM-1, CD161, NKp46 and NKp30 activating receptors while inhibitory receptors CD85j and NKG2A were over-expressed. This inhibited phenotype affected cytotoxic functionality against CRC cells and IFN-γ production. We also determined that NKp30 and NKp46 are the key receptors involved in detriment of CRC-NK cells anti-tumor activity. Moreover, NKp46 expression correlated with relapse-free survival of CRC patients with a maximum follow-up of 71 months. CRC-NK cells also exhibited altered antibody-dependent-cellular cytotoxicity function responding poorly to cetuximab. IL-2 and IL-15 in combination with cetuximab stimulated NK cell improving cytotoxicity. These results show potential strategies to enhance CRC-NK cell activity.